VERBAL AND NONVERBAL ASPECTS IN REALIZING LANGUAGE POLITENESS IN THE FILM “SABTU BERSAMA BAPAK” MADE BY ADHITYA MULYA - Prima Gusti Yanti,; Deasy Wahyu Hidayati,; Nini Ibrahim, (International Journal of Social Science, 2022)
This study aims to describe the verbal and nonverbal aspects of the Realization of Language Politeness in the film "SabtubersamaBapak" by Adhitya Mulya and it was designed by using a qualitative descriptive method with content analysis techniques. This qualitative descriptive method is used to collect and compile data, analyze and interpret data (Rukajat, 2018). By using a qualitative descriptive method, the researcher simply analyzed data based on verbal and nonverbal language politeness in the film "SabtubersamaBapak" by AdhityaMulya. The results showed that the most dominant language politeness in verbal communication appears in the film the film "Sabtu bersama Bapak" are sympathy and wisdom. Meanwhile, language politeness in non-verbal communication is dominant in kinesics, namely gestures, hands, head, and so on.